An existence theorem for an implicit integral equation with discontinuous right-hand side - Anello Giovanni (Journal of Inequalities and Applications, 2006)
We establish a result concerning the existence of solutions for the following implicit integral equation: , where is not supposed continuous with respect to the second variable.